The relationship of Kuala Lumpur composite index and macroeconomic variables: comparison between Asian financial crisis and global financial crisis / Farah Athirah Md Zulkiflie - Md Zulkiflie, Farah Athirah (2016)
This paper aims to investigate which crisis gave more impact towards the relationship of KLCI in Malaysia and macroeconomic variable. The objective in this research is to study the relationship between macroeconomic variables and KLCI. Selected macroeconomic variables are Money supply, inflation rate, interest rate and gross domestic product. Also to study which situation that gave most impact towards KLCI. The dependent variable is the main variable and interest that researcher want to investigate and measure the effect of independent variables on dependent variable. The dependent variable on this study is Kuala Lumpur Composite Index. So, this study is to investigate the relationship of macroeconomics selected towards KLCI. The independent variables mean the one that can influence and effect on dependent variable. In this research, the study is to investigate the relationship between dependent and independent variables that is gross domestic product, money supply, inflation rate, and interest rate. Variables for this study is Malaysian stock market index as the base variables or known as dependent variable and the independent variables for this study are interest rate, inflation rate, money supply and gross domestic product. Conducting the study will be considered the information and data from the Thompson DataStream provided by UiTM library database. This study covered a period from 1st January 1996 until the end of 2014, We use the monthly closing price of the Kuala Lumpur Composite Index (KLCI) to analyze the volatility.